SISTEM INFORMASI LAYANAN PEMINJAMAN DAN PEMBAYARAN KEUANGAN PADA PT BPR NBP 8 CABANG TIGALINGGA - Sihombing, Elsa Cristina; Hutapea, Marlyna I.; Nainggolan, Rena (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The Information System is very useful for PT BPR NBP 8 Tigalingga Branch because it can simplify and speed up work processes on the system. The previous system still used the manual method, namely recording data by writing in a book. At PT BPR this is very useful in carrying out its activities so it is very helpful for officers. This information system assists officers in storing financial reports, data, and with this system it can be easier or safer. In making database information system databases at BPR, it really needs an implementation process design. The database information system will be used to record information on lending services and financial payments at bpr nbp. The process of making a loan and payment information system will be designed using a Web Server application, XAMPP, Sublimenttext 3, Web Browser. Based on the analysis of the previous system, it was very common to have errors in bookkeeping and experienced many errors, so currently using an information system that has been designed that will help officers more easily, quickly, even more secure and will not experience errors again.